Village Government and Religious Affairs Office (KUA) Policies in Reducing Early marriage in Southern Bangka - Suryadin, Asyraf; Haiyudi, Haiyudi; Saputra, Adi (Universitas Muhammadiyah Magelang, 2024)
The province of Bangka Belitung is known as one of the regions with significantly high rated early marriage. This study is focused on the development of Payung village government collaboration with Religious Affair Office in reducing the number of early marriages. this research adopts qualitative method and apply historiography-phenomenology approach which includes four phases: heuristic, verification or source evaluation, interpretation, and historiography. The research location is Payung village, South Bangka. The research includes in-depth interview with the village head, Village Consultative Body, and the head of Religious Affairs Office. The research results are realized in three village regulations. They are Village Regulation Number 2 of 2020 concerning villages that support children's rights, Village Regulation Number 3 of 2020 concerning child protection, and Village Regulation Number 141 of 2022 concerning child-friendly village development. Other than that, innovations such as refusion of early marriage recommendation letter, regular counseling at schools regarding early marriage and the consequences, a ban on using village facilities for early marriage ceremonies, and a policy for village officials not to attend early marriages, are also implemented. These new policies have proven effective in reducing the rate of early marriage. Researchers hope that these innovations can be used as models by other villages or regions in the efforts to reduce the rate of early marriage.